Liquidity Management Requirement and Financial Performance of Commercial Banks in Rwanda: A Case of Bank of Kigali - Safi , Buhangu; Muiruri, Paul Munene; Ernest, Safari (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2021)
liquidity demands from depositors and borrowers of credit are not too correlated, an intermediary reduces its cash buffer by serving both customers. The study looked at effects of liquidity management requirement on commercial banks' financial performance in Rwanda a case of the bank of Kigali. The study specifically focused on: effect of credit risk, capital requirement, as well as liquidity requirement on banks' financial performance in Rwanda from 2016 to 2020. This research will help the learner get her master’s degree in finance as it is the requirement to get this degree; not only this but also by going through the literature review, the empirical review, and all steps of the research process, the researcher research skills will be high and empowered for the future field research. The study also provided different recommendations of the strategies that will be necessary and essential to be implemented in banks to achieve their financial performance. The 110 sizes were chosen through systematic random sampling and stratified sampling method from the population, and the data was gathered from respondents through questionnaires; documentary analysis was also used. Data were tabulated, coded, analyzed, and interpreted using SPSS (Version 22.0). The research revealed that at bank of Kigali, use of prudential loan management strategies has a significant positive association with the performance of a bank of Kigali as it is being indicated by the views of liquidity management requirement relates positively with financial performance of bank of Kigali and the relationship is significant since (?=0.225, p<0.5; p=0.000).from multiple regression analysis. The research concluded that loan management strategies greatly influences financial performance as justified by the high mean and homogeneity standard deviation of the variables and positive P-Values obtained from multiple regression analysis.